Stimulation of IgM Production in HB4C5 Cell Line and Mouse Splenocytes by Egg Yolk Extract from the Egg of Indonesian Native Chicken - R. Mulyani; E. Harmayani; Nurliyani; K. Nishi; M. Ishida; T. Sugahara (Faculty of Animal Science, Bogor Agricultural University, 2021)
Kampung-chicken, as a local wisdom, has always been considered superior in terms of health benefits compared to commercial chicken. Therefore, this study was designed to evaluate the immunostimulatory effects of Kampung-chicken eggs using in vitro approaches. The physical (interior and exterior quality) and chemical characteristics of Kampung-chicken eggs were firstly analyzed; the commercial chicken egg was used as a comparison. The effects of water extract of Kampung-chicken egg yolk (KEYWE) and water extract of commercial-chicken egg yolk (CEYWE) on IgM production and the expression of IgM-gene on HB4C5 cells were analyzed. In addition, the stimulatory effects of both samples on IgA, IgG, and IgM production by mouse primary splenocytes were analyzed as well. To isolate the active substance, the water extract from egg yolk was partially purified by salting out using (NH4)2SO4. Data analysis of the comparison between Kampung-chicken egg and the commercial-chicken egg was performed by t-test; meanwhile, the results for in vitro studies were performed by one-way ANOVA, and Tukey’s multiple comparison test was used for posthoc analysis. The result showed that KEYWE increased IgM production in HB4C5 cells by 5.91 fold as compared with control. In addition, KEYWE increased IgA, IgG, and IgM productions in mouse primary splenocytes by 5.20, 2.54, and 3.1 fold, respectively. Moreover, the immunoglobulin (Ig) production-stimulating activities of KEYWE on HB4C5 cells and mouse primary splenocytes were higher than those of CEYWE. The active substance in Kampung-chicken egg yolk was precipitated at 80% saturation of (NH4)2SO4. Altogether, it is expected that the Kampung-chicken egg has more effective immunostimulatory activity than the commercial chicken egg.